AKTIVITAS KEAGAMAAN SISWA DAN JARINGAN MENTORING ROHIS SMA NEGERI DI KABUPATEN SUKOHARJO Students’ Religious Activity and Mentoring Network of Rohis at Senior High School in Sukoharjo District - Aji Sofanudin (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Religious knowledge, religious attitude, and religious behavior of student were influenced by formal and non formal education. In the senior high school, Rohis have a big role to transfer knowledge, attitude, and religious behavior of students. With qualitative approach, this research aims to describe knowledge, attitude, and religious behavior of Senior High School students (SMA) and mentoring network of Rohis SMA at Sukoharjo District. This research found that religious concept according to students in the Sukoharjo District is diverse. They join with different organizations such as NU, Muhammadiyah, MTA, and LDII. In general, religious attitude of students are tolerance. Religious behavior is reflected in their daily activities which are categorized as in good category. Mentoring network of Rohis SMA shows three models: (1) teacher model, this model includes Islamic religious education teacher or coach of Rohis, (2) Student model, this type is through alumni or joining with student activity unit, and (3) Society model, this mentoring was held by NGO like LPR Pioner and LPP Gemilang.